Troubled watchdogs: the paradox of journalism in Chinese media orgnanisations based in Africa - Umejei, Emeka Lucky (My University, 2017)
This thesis examines how African journalists negotiate the tension between their understanding of journalism and the actual practice of journalism within the context of Chinese media organisations based in Africa. Adopting the Shoemaker and Reese (1996) hierarchy of influences model and using interviews with African journalists in Kenya and content analysis, I examine this tension within the framework of the relationship between role conception and role performance. China has framed its media expansion into Africa on the premise that it aims to tell the ‘true African story’ to global audiences. This is consistent with China’s Africa policy promising mutuality and equality between China and Africa. However, the findings indicate an African and a Chinese level of gatekeeping and journalistic agency exist within Chinese media organisations based in Africa. These levels often coexist, but they also collide, resulting in Chinese interests and ideas prevailing over those of African journalists, and often in a type of journalism that de-emphasises African belonging and identity. This study represents an original contribution to the debate on the relationship between role conception and role performance, from a non-western perspective. It demonstrates the ways in which the relationship between role conception and role performance within Chinese media organisations in Africa is hinged upon conditional autonomy in relation to the typology of stories. The elements of the hierarchy of influences model are more active when Chinese interests are present in a story than when they are absent. Consequently, the editorial policy of ‘positive reporting’ promoted by Chinese media organisations is more active in the coverage of activities related to China than non-China content. This thesis enriches the five levels of analysis in Shoemaker and Reese’s hierarchy of influences model. This study proposes language as a level of influence straddling media routines and organisation influences, when applied to Chinese media organisations in Africa. This thesis also contributes to the ideologisation debate on Chinese media expansion into Africa. While the debate has been dominantly framed through the Manichean prism of positive or negative, this thesis proposes Chinese media expansion into Africa will result in a hybrid form of journalism professionalisation in which Western and Chinese journalistic traditions co-exist on the continent.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Doctor of Philosophy, March, 2017.
Keywords: Mass media--China; Mass media--Africa; Africa--Press coverage--China--Congresses; Africa--Relations--China--Congresses; China--Relations--Africa--Congresses